PENGARUH BUDAYA ORGANISASI DAN PENGEMBANGAN ORGANISASI (Studi Kasus Karyawan PT. Suka Fajar Cab. Pekanbaru) - Gabriela Ningrum Natalia; Seno Andri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to analyze organizational culture and career development and its influence on organizational commitment of the PT. Suka Fajar Subs. Pekanbaru. Organizational Culture as a variable (X1), Career Development as a variable (X2), and Organizational Commitment as a variable (Y). The method in this research is descriptive quantitative by using SPSS 21, where in the sample used are employees of 68 is done, by purposive sampling method and technique of data collection through questionnaires.The results of the analysis using validity test, reliability test, determination test, simple linear regression test, multiple linear regression test, t test and F test. it can be concluded that organizational culture have a significant effect on organizational commitment of the PT. Suka Fajar Subs. Pekanbaru, career development have a significant effect on organizational commitment of the PT. Suka Fajar Subs. Pekanbaru, as well as organizational culture and career development have a significant effect on organizational commitment of the PT. Suka Fajar Subs. PekanbaruKeywords: Organizational Culture, Career Development, and Organizational Commitment